2012
DOI: 10.1002/ibd.21690
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Feeding Therapy for Newly Diagnosed Pediatric Crohnʼs Disease: A Double-Blind Randomized Controlled Trial with Two Years Follow-Up§

Abstract: There was no significant difference between EF and PF in inducing remission. One-third of children maintained remission. Changes in plasma polyunsaturated fatty acid status were subtle and may be relevant; however, further evaluation is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 24 publications
2
69
1
8
Order By: Relevance
“…The most popular theory was that elemental diets had a reduced antigenic load to the inflamed bowel compared with full protein feeds [O'Sullivan and O'Morain, 1998]. However, this may not be the case because polymeric feeds have since been found to be equally efficacious [Zachos et al 2007;Grogan et al 2012]. In addition, because polymeric feeds are more palatable than elemental feeds, the former tend to be used first line.…”
Section: Induction Of Remission: Enteral Nutritionmentioning
confidence: 99%
“…The most popular theory was that elemental diets had a reduced antigenic load to the inflamed bowel compared with full protein feeds [O'Sullivan and O'Morain, 1998]. However, this may not be the case because polymeric feeds have since been found to be equally efficacious [Zachos et al 2007;Grogan et al 2012]. In addition, because polymeric feeds are more palatable than elemental feeds, the former tend to be used first line.…”
Section: Induction Of Remission: Enteral Nutritionmentioning
confidence: 99%
“…Clinical trials comparing EEN to steroids based on remission rates as outcome parameter showed an overall remission rate of approximately 75% for EEN at the end of exclusive treatment. Remission rates with steroids were not different from EEN-induced remission in these two meta-analyses based on a total of 11 pediatric clinical trials [32][33][34][35][36][37][38][39][40][41] . A further pediatric study has recently been published [41] , showing data in line with the previous studies.…”
Section: Efficacy Of Een As Treatment Option For CDmentioning
confidence: 99%
“…em DC ativa 35,36 . Em ambos, ω3 foi incluído na fórmula enteral para ser usado como suplemento ou nutrição enteral total.…”
Section: Dois Estudos Foram Identificados Sobre O Efeito Do ω3unclassified
“…Não foi realizada avaliação endoscópica do efeito da terapia. O segundo experimento foi conduzido em pacientes pediátricos 36 . O estudo comparou duas fórmulas enterais como tratamento primário para DC ativa sem nenhuma outra terapia.…”
Section: Dois Estudos Foram Identificados Sobre O Efeito Do ω3unclassified
See 1 more Smart Citation